1992
DOI: 10.1016/0014-5793(92)80644-v
|View full text |Cite
|
Sign up to set email alerts
|

Transcripts of the viroid central conserved region contain the local tertiary structural element found in full‐length viroid

Abstract: The viroid central conserved region (CCR) is highly conserved among different viroids and is thought to be involved in viroid replication. A novel tertiary structure occurs in the CCR of native circular potato spindle tuber RNAs. To permit more detailed studies of this structural clcmcnt. a sITX$ll RNA oligonucleotide containing the CCR of the viroid genomc was synthesized. The tertiary structureof these CCR transcripts wasexamined by UV-crosslinking of the RNA, followed by mapping of the crosslink using limit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1995
1995
2016
2016

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…Biochemical studies on loop B and NMR studies on model oligonucleotides have revealed a complex pattern of Watson‐Crick and non‐canonical base‐pairs (Wimberly et al ., 1993; Butcher and Burke, 1994b; Szewczak and Moore, 1995). Branch and colleagues deduced the loop E‐like motif in viroids from a characteristic UV crosslink between the two bases G 98 and U 260 located in opposite strands of the CCR (Branch et al ., 1985; Paul et al ., 1992).…”
Section: Resultsmentioning
confidence: 99%
“…Biochemical studies on loop B and NMR studies on model oligonucleotides have revealed a complex pattern of Watson‐Crick and non‐canonical base‐pairs (Wimberly et al ., 1993; Butcher and Burke, 1994b; Szewczak and Moore, 1995). Branch and colleagues deduced the loop E‐like motif in viroids from a characteristic UV crosslink between the two bases G 98 and U 260 located in opposite strands of the CCR (Branch et al ., 1985; Paul et al ., 1992).…”
Section: Resultsmentioning
confidence: 99%
“…To produce alkaline hydrolysis ladders, samples were incubated at 90°C in 0.05 M sodium bicarbonate/carbonate at pH 9.2 for either 15 min (lanes a, d and e) or 5 min (lanes b, c and f). To produce a family of RNase TI partial digestion products, non-crosslinked samples were incubated at 65°C in buffer containing RNase TI and urea for 15 min (lane g) or4 min (lane h), as described before (62). Each band in the alkaline ladder is marked by a dot, to assist in the counting of the bands.…”
Section: U Cmentioning
confidence: 99%